Antimicrobial effects and membrane damage mechanism of blueberry (Vaccinium corymbosum L.) extract against Vibrio parahaemolyticus. (May 2020) - Sun, Xiao-hong; Hao, Li-ran; Xie, Qing-chao; Lan, Wei-qing; Zhao, Yong; Pan, Ying-jie; Wu, Vivian C.H.
Abstract: This study aimed to investigate the antimicrobial effect and membrane damage mechanism of blueberry extract against Vibrio parahaemolyticus . The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of blueberry extract against three strains of V. parahaemolyticus were determined. The antimicrobial activity of blueberry extract on V. parahaemolyticus inoculated in salmon was evaluated. The effect of blueberry extract on V. parahaemolyticus cell membrane was visualized by scanning electron microscopy and transmission electron microscopy. We examined the antimicrobial mechanism of blueberry extract in the regulation of the seven membrane genes expression. The MIC for V. parahaemolyticus ATCC 17802, ATCC 33847 and F 13 was 25, 25 and 12.5 mg/mL, respectively, whereas the MBC was 50, 50 and 25 mg/mL, respectively. The blueberry extract has antimicrobial effect on V. parahaemolyticus in salmon samples. The V. parahaemolyticus exposed to 1 × MIC showed distorted membrane morphology and leakage of cellular contents. The cytoplasmic constituents were aggregated, causing a wide range of hollow areas in the cells. The expression of seven membrane genes in V. parahaemolyticus treated with blueberry extract was investigated by quantitative real-time PCR. Compared to that in the control, the gene expression of fadL and nusA was upregulated by 1.1-, 2.1-, 4.1-fold and 7.4-, 4.3-, 3.6-fold in V. parahaemolyticus ATCC 17802, ATCC 33847 and F 13, respectively. The gene expression of ef-Tu was downregulated by 1.1-, 2.7-, 3.3-fold in the three strains of V. parahaemolyticus. Findings from this study revealed that blueberry extract had strong antibacterial effect and inhibited gene transcription to disrupt cell membrane structure and energy transport. Further studies investigating potential antimicrobial applications of blueberry extract are necessary to provide a basis for the development and utilization of blueberries as an antimicrobial agent. Highlights: Blueberry extract showed antimicrobial effect against V. parahaemolyticus strains. Blueberry extract disrupted bacterial cell membrane integrity. Blueberry extract interrupted normal growth of bacterial cells. Blueberry extract altered the expression of seven membrane genes.